An experimental investigation of hybrid manufactured SLM based Al-Si10-Mg alloy under mist cooling conditions. (October 2021) - Ramoni, Monsuru; Shanmugam, Ragavanantham; Ross, Nimel Sworna; Gupta, Munish Kumar
Abstract: Focus on lightweight materials like aluminium, titanium etc. are growing as a reason of its eminent strength, resistance to corrosion, and less weight. Employing additive manufacturing (AM) process to fashion complex parts is increasing day-to-day. AlSi10Mg handled by laser-based powder bed fusion (LPBF) is an emerging material because of its high performance and reduced coefficient of thermal expansion due to the presence of silicon. However, AM process shows several advantages, poor surface quality is a mere disadvantage, which requires a post processing. The machining of LPBF parts for improving their quality is a difficult task as a reason of component orientation and layer thickness (LT). Recently, a new trend has developed, AM process combined with subtraction of materials to get good surface characteristics. This holistic investigation addresses problems like surface morphology, tool wear and temperature with varied cooling techniques (Dry, Flood and MQL) while machining AM-AlSi10mg work material. Generation of heat at the cutting region is responsible for surface deterioration and frequent change of tools. Compared to dry and flood condition, the MQL improved the surface trait by 45–63% and 23–43%; flank wear by 45–29% and 18–31%, respectively. SEM images show flakes in all the cutting environments. It has also been established that MQL method increases microhardness on the machined face by removing the heat in the cutting region.